Improved Analysis of DVR Performance for Voltage Sag Mitigation - Abdul Razak, Hannah Naqiah; Mat Said, Dalila; Ahmad, Nasarudin (ELEKTRIKA- Journal of Electrical Engineering, 2018)
Dynamic Voltage Restorer (DVR) provides the most reliable solution to the voltage quality problem in power distribution system from the effectiveness of DVR performance for voltage sag mitigation. As a custom power device, DVR offers the best solution to three phase power system in order to improve the power quality issue as the magnitude and phase of the voltage is added during the sags occurrence to restore the load condition to compensate the voltage sags. The suitable controller, Proportional-Integral (PI) Controller is used along with the Pulse Width Modulation (PWM)-based control scheme to calculate the exact error and generate the missing voltage to be injected to the three-phase power system through injection transformers. Simulation results of various fault types using MATLAB/SIMULINK are shown in this paper to demonstrate the successful compensation of voltage sags by mitigation technique using Dynamic Voltage Restorer in three-phase power distribution.Â